Entangled signal pathways can both control expression stability and induce stochastic focusing. Issue 7 (28th February 2018) - Wang, Haohua; Liu, Peijiang; Li, Qingqing; Zhou, Tianshou
Abstract : Gene transcription is often controlled by multiple interacting signal pathways, but how these pathways impact gene expression is not fully understood. Here, we refine a mechanic model based on experiments in murine embryonic stem cells and analyze the influence of pathway–pathway cross‐talk strength (CTS) on mRNA expression stability. We find that the CTS can tune this stability, depending on the manner of regulation. Furthermore, there is an optimal CTS such that the expression pattern is most stable but free energy consumption is at its highest; the CTS can induce stochastic focusing of the mRNA level but this is at the cost of energy. In both cases, there is a cross–talk‐mediated trade‐off, implying that entangled signal pathways can control both expression stability and energy dissipation. Abstract :